Tissue adhesion type cartilage double-layer artificial auricle material based on multi-coating and UV curing process and preparation method of tissue adhesion type cartilage double-layer artificial auricle material

By using a multi-coating and UV curing process to prepare a tissue-adhesive, chondrogenic, double-layer artificial auricle material, the problems of poor adhesion between the artificial auricle and surrounding tissues and excessively rapid drug release were solved, achieving better tissue adhesion and chondrogenic effects.

CN121288005APending Publication Date: 2026-01-09ZHEJIANG PROVINCIAL LITONGDE HOSPITAL (ZHEJIANG PROVINCIAL INST OF MENTAL HEALTH)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511593510.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-03
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing technologies suffer from poor fit between artificial auricles and surrounding tissues, as well as the problem of excessively rapid release of cartilage-promoting drugs, which affect aesthetics and cell migration.

Method used

A tissue-adhesive, chondrogenic, bilayer artificial auricle material was prepared using a multi-coating and UV curing process. The outer layer is a HAMA-DA layer that provides adhesion, while the inner layer is a composite material layer of MSCs/drug-loaded HAMA microspheres/porous GelMA. By combining microfluidic technology and photocuring process, chondrogenic drugs are loaded and slowly released.

Benefits of technology

It improves the fit and stability of the artificial auricle with surrounding tissues, promotes cell migration and chondrogenesis, reduces inflammatory response, and achieves efficient in-situ reconstruction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121288005A_ABST
    Figure CN121288005A_ABST
Patent Text Reader

Abstract

The invention discloses a tissue adhesion type cartilage double-layer artificial auricle material based on a multi-coating and UV curing process and a preparation method of the tissue adhesion type cartilage double-layer artificial auricle material. The method comprises the following steps: (1) preparing methacrylic acid hyaluronic acid (HAMA) microspheres loaded with Kartogenin by adopting a microfluidic-impregnation technology; (2) synthesizing dual-modified HAMA-DA with a dopamine function and a photo-crosslinking capability through a coupling reaction of methacryloylation and carboximide; 3) preparing a high-fidelity artificial auricle mold through photocuring 3D printing based on LiDAR and a three-dimensional reconstruction technology; 4) preparing a methacrylic acid gelatin (GelMA) composite slurry of the composite mesenchymal stem cells and the drug-loaded HAMA microspheres; 5, the surface of the mold is sequentially coated with a glycerol layer, an HAMA-DA solution layer, a GelMA composite slurry layer and an HAMA-DA solution layer for multiple times, UV pre-curing and secondary UV curing are matched in the coating process, and the double-layer auricle structure with the wet tissue adhesiveness and the cartilage induction potential is obtained.According to the system, an advanced material platform and a process path are provided for artificial auricle construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of 3D modeling and printing and artificial auricle materials, specifically to a tissue-adhesive chondrogenic bilayer artificial auricle material based on multiple coating and UV curing processes and its preparation method. Background Technology

[0002] The auricle is one of the most complex three-dimensional structures in the human body, so constructing a satisfactory and complete external ear for patients with microtia or large auricular defects has been a long-standing goal for otolaryngologists. Auricular reconstruction utilizes a subcutaneous support structure to maintain the ear's delicate anatomical structure. Currently, the support structures for auricular reconstruction mainly include auricular scaffolds sculpted from the patient's homologous rib cartilage, Medpor prefabricated scaffolds, and tissue-engineered cartilage auricular scaffolds. Autologous rib cartilage sculpted auricular scaffolds are the most widely used in clinical practice, but they suffer from donor site damage and are highly dependent on the surgeon's technique and aesthetic sense. Due to the limitations of autologous cartilage scaffolds, and with the rapid development of tissue engineering and 3D printing technology in recent years, bio-scaffolds made from natural materials, synthetic materials, or hybrid materials are increasingly becoming promising solutions for auricular reconstruction.

[0003] Compared to synthetic materials, natural materials (such as hyaluronic acid and alginate) have better biocompatibility and are well-suited for constructing three-dimensional morphologies. The addition of specific growth factors can effectively promote cell chondrogenesis and proliferation. However, some drawbacks remain. For example, tissue-engineered auricles may slip or shift after implantation, or gaps may exist between the implant and surrounding tissues. This can lead to poor aesthetics, affect cell migration and cytokine interaction between the material and surrounding tissues, potentially causing the death of encapsulated stem cells. Furthermore, gaps between the artificial auricle and surrounding tissues can increase the risk of infection. Therefore, endowing the artificial auricle with surface adhesive properties is a solution to increase its adhesion to surrounding tissues and reduce the risk of infection.

[0004] Secondly, traditional methods involve directly encapsulating stem cells and chondrogenic factors in hydrogels for implantation. This can lead to the rapid release of chondrogenic factors, affecting the chondrogenic capacity of the artificial auricle. Furthermore, the direct encapsulation of stem cells can hinder their migration within the hydrogel. Hydrogel microspheres, on the other hand, are a novel hydrogel morphology with unique properties. For example, they can be used to load drugs for controlled drug release. Moreover, compared to traditional hydrogels, these microspheres have a higher porosity, exhibiting enhanced cell migration and infiltration of cells from surrounding natural tissues in both in vitro and in vivo environments.

[0005] To address the aforementioned issues, this invention combines various advanced tissue engineering techniques. Building upon current 3D reconstructed auricles and cell-carrying hydrogels, it adds an outer layer with tissue adhesion properties. This results in better tissue fit after implantation, reducing gaps between the implanted auricle and surrounding skin, and further enhancing cell migration and cytokine interaction between the material and surrounding tissues. Simultaneously, the inner layer of the artificial auricle utilizes hydrogel microspheres loaded with chondroitinizing drugs. As the microspheres degrade, the drugs are slowly and quantitatively released, better promoting the continuous differentiation of stem cells into chondrocytes within the hydrogel. Furthermore, based on lidar and 3D reconstruction technology, this invention provides a more precise auricle reconstruction scheme and utilizes a casting method to obtain the desired artificial auricle, avoiding cell compression and thermal damage during 3D printing of cell-carrying hydrogels. Summary of the Invention

[0006] The purpose of this invention is to address the problems that may occur in the prior art, such as poor adhesion between artificial auricles and surrounding tissues and excessively rapid release of cartilage-promoting drugs. By combining the advantages of various materials and processes, this invention provides a tissue-adhesive chondrogenic bilayer artificial auricle material based on multiple coating and UV curing processes, and its preparation method.

[0007] This invention is achieved using the following technical solution: A method for preparing a tissue-adhesive, chondrogenic, bilayer artificial auricle material based on multiple coating and UV curing processes includes the following steps: 1) Using microfluidic technology combined with impregnation process, methacrylated hyaluronic acid (HAMA) microspheres loaded with Kartogenin were constructed to obtain drug-loaded HAMA microspheres; 2) HAMA-DA molecules modified with dopamine and methacrylamide bifunctional groups were synthesized by methacrylation and carboxylimide coupling reaction, and the resulting solution was prepared to obtain HAMA-DA solution. 3) Based on LiDAR and 3D reconstruction technology, a high-fidelity artificial auricle mold is prepared by photopolymerization 3D printing; 4) Prepare a gelatin methacrylate (GelMA) solution and combine it with mesenchymal stem cells (MSCs) and drug-loaded HAMA microspheres under aseptic conditions at 35-37℃ to obtain a GelMA composite slurry; 5) Perform a multi-coating process on the mold surface: sequentially coat a glycerol layer, a HAMA-DA solution layer, a GelMA composite slurry layer containing MSCs and drug-loaded HAMA microspheres, and a HAMA-DA solution layer. During the coating process, perform preliminary UV curing and UV curing shaping, demold, rinse, and dry to obtain the artificial auricle material.

[0008] In the above technical solution, further, in step 1), the microfluidic technology involves using a 3-5 wt% HAMA solution as the dispersed phase and Novec 7500 fluorinated oil as the continuous phase at 35-37°C. The flow rate of the dispersed phase is controlled at 2-4 µL / min, and the flow rate of the continuous phase is controlled at 10-20 µL / min to form a W / O microemulsion (HAMA microdroplet diameter approximately 50-100 µm). This microemulsion is then cross-linked and cured by UV irradiation, followed by diethyl ether phase separation, washing with deionized water, and freeze-drying to obtain HAMA microspheres. The UV irradiation source is 350-410 nm with a power of 20-40 mW / cm². 2 Irradiation time: 120-180 seconds.

[0009] Furthermore, in step 1), Kartogenin loading is achieved through an impregnation process: HAMA microspheres are placed in a 0.1-0.2 mM Kartogenin / DMSO solution at 4-8°C and impregnated in a sealed environment for 6-24 h, and then aged for 6-12 h, followed by rinsing with PBS to complete the drug loading of HAMA microspheres.

[0010] Further, in step 2), the HAMA-DA is prepared by a dual chemical grafting reaction: 1-2 wt% HA is dissolved in deionized water, the pH of the solution is adjusted to 7-8, and 20-25 times the molar excess of methacrylic anhydride relative to the hydroxyl group of HA is added. After reacting at room temperature for 4-6 hours, the solution is transferred to 4 °C and reacted for another 15-25 hours. After precipitation in cold ethanol, centrifugation, washing, and lyophilization, HAMA is obtained. Further, 1-2 wt% HAMA is dissolved in deionized water, the pH of the solution is adjusted to 4-5, and EDC / NHS is added to perform a secondary dopamine grafting modification with dopamine hydrochloride via a carboxyimide coupling reaction. The reaction is carried out in the dark for 4-8 hours, and the solution is transferred to deionized water for dialysis for 3-5 days, with the solution changed 3-6 times a day. After lyophilization, HAMA-DA is obtained.

[0011] Furthermore, the molar ratio of EDC, NHS, and HAMA is 2:1:2-2:1:4, and the molar ratio of HAMA to dopamine hydrochloride is 1:0.5-1:1. When dialyzing HAMA-DA, the molecular weight cutoff of the dialysis bag is 3.5 kDa. HAMA-DA is dissolved in deionized water to prepare a solution with a concentration of 3-5 wt%, and a photoinitiator is added at a concentration of 0.1-0.25 wt%. The dissolution process is carried out under light-protected conditions and at room temperature. The photoinitiator can be one or more of LAP, Irgacure, and I2959.

[0012] Furthermore, in step 3), depth data and multi-view pose information of a healthy auricle are first collected using a LiDAR-equipped mobile device. Then, one or more methods based on multi-view stereo vision (MVS), Gaussian mixture model, and depth map fusion are used to fuse the multi-view images and depth information to generate an initial 3D model of the auricle. Subsequently, a point cloud / mesh super-resolution network (including but not limited to PU-Net, MPU, PU-GAN) is used to upsample the point cloud data corresponding to the initial 3D model and perform a feature-preserving remesh operation to improve the sampling density and geometric fidelity in the required areas. Then, based on the obtained refined 3D model, a negative mold structure is designed to obtain a high-precision, smooth-surfaced, and structurally complete 3D model of the artificial auricle casting mold. Finally, transparent photosensitive resin is used as the raw material, and 3D photopolymerization printing technology is used to print the transparent artificial auricle casting mold. After the mold is formed, it is polished until the surface roughness is less than 0.2µm. Among them, the transparent photosensitive resin is one of the following: transparent PETG (polyethylene terephthalate-1,4-cyclohexanediol ester), transparent nylon, transparent ABS (acrylonitrile (A)-butadiene (B)-styrene (S) terpolymer).

[0013] Further, in step 4), a porous GelMA solution with a concentration of 5-7.5 wt% is prepared by dissolving in a water bath at 60-80℃ under light-protected and sterile conditions. After complete dissolution, the solution is cooled to 35-37℃, filtered for sterilization, and P2-P4 generation MSCs and drug-loaded HAMA microspheres are added. The solution is then blown to homogenize, and a photoinitiator is added to obtain the GelMA composite slurry.

[0014] Furthermore, the concentration of MSCs in the GelMA composite slurry is 1×10⁻⁶. 7 The concentration of drug-loaded HAMA microspheres was 3-5 wt%; the concentration of photoinitiator was 0.1-0.25 wt%.

[0015] Further, step 5) specifically involves: firstly, coating the surface of the artificial auricle mold with a glycerol layer; then coating a HAMA-DA solution layer with a thickness of 0.25-1 mm (the coating thickness can be determined according to the mold and by controlling the amount of coating solution), and pre-curing with UV for 10-15 seconds; then coating the porous GelMA composite slurry on top, and pre-curing with UV for 10-15 seconds; then coating the free surface of the pre-cured slurry with a HAMA-DA layer with a thickness of 0.25-1 mm, and finally curing and shaping for 15-20 seconds; then shaking the cured artificial auricle to demold it, rinsing it with PBS and drying it with sterile nitrogen to obtain the artificial auricle material.

[0016] Compared with the prior art, the present invention has the following advantages: 1) This invention uses bioactive materials such as drug-loaded HAMA microspheres, porous GelMA, and HAMA-DA as a base, loads mesenchymal stem cells, and combines multiple chemical grafting, microfluidic technology, multiple coating process, in-situ photocuring method and drug controlled release and other combined processes to prepare a tissue-adhesive chondrogenic double-layer artificial auricle structure. This material system and composite preparation strategy are innovative.

[0017] 2) Innovative Process Combination: This invention utilizes methacrylation and carboxyimide coupling reactions to synthesize a HAMA-DA double-grafted polymer material that simultaneously possesses wet adhesion to surrounding tissues and photocurability. The casting mold preparation innovatively employs LiDAR to collect multi-view depth data of the auricle, followed by 3D fusion, point cloud super-resolution, and feature-preserving remeshing processing to construct a high-precision auricle model. Based on this, a transparent resin casting mold is designed and prepared using photocuring 3D printing technology. Compared to existing technologies, this method significantly improves the accuracy of auricle morphology acquisition, the conformity of the formed structure, and the fidelity of auricle detail reproduction, achieving a highly realistic reconstruction of the natural auricle structure. Furthermore, this invention employs multiple coatings when using the casting method to fabricate the artificial auricle. The process begins with a glycerol-based insulating layer to ensure undamaged demolding of the outermost layer of the artificial auricle structure after molding. The intermediate layer is a HAMA-DA adhesive layer, designed to ensure good adhesion between the subsequently coated MSCs / drug-loaded HAMA microspheres / porous GelMA composite material and the implanted skin tissue. Compared to the insufficient precision in controlling the thickness of artificial auricle layers and the risk of structural deformation inherent in traditional single-casting processes, the multi-coating-in-situ photocuring process employed in this invention enables precise control of the thickness of each functional layer of the artificial auricle. This ensures uniform material distribution on the complex curvature of the mold surface, thereby fully guaranteeing and optimizing the preset performance of each functional layer, perfectly replicating the morphology of the natural auricle, and effectively helping patients solve their practical problems. Although the aforementioned single process already has related applications in relevant fields, in this invention, the processes are synergistically combined according to actual experimental needs to successfully construct the artificial auricle structure, realizing a new application of the old process.

[0018] 3) Innovation in synergistic structure and function: The fabricated artificial auricle has a double-layer structure: the outer layer is a HAMA-DA layer, which has wet adhesion to tissues, allowing the auricle to fit well with the tissue after subcutaneous implantation, preventing local displacement and auricle-subcutaneous gap. At the same time, the photocuring properties of HAMA-DA can provide mechanical support and protection for the inner layer cells and materials. In addition, HAMA-DA molecules also have antioxidant and anti-inflammatory functions, which can alleviate the inflammatory and oxidative stress response caused by implantation of the artificial auricle to a certain extent. The inner layer is a composite material layer of MSCs / drug-loaded HAMA microspheres / porous GelMA. The presence of microspheres can not only release the loaded drug over a long period of time, but also provide certain mechanical support for the inner layer materials after photocuring. The loaded drug Kartogenin has a better ability to promote the differentiation of MSCs into chondrocytes than traditional chondrocyte differentiation factors, and increases the expression of chondrocyte-specific genes. In addition, porous GelMA provides porous channels inside the middle layer, which can promote the migration of stem cells, facilitate the exchange of substances and oxygen, and improve the survival rate of internal cells. Through the synergistic effect of the above-mentioned dual-layer structure, the artificial auricle can have better integration / fixation ability with surrounding tissues, tissue compatibility and cartilage formation ability, thereby achieving efficient in-situ reconstruction of the patient's auricle.

[0019] 4) This invention innovatively introduces a HAMA-DA solution layer (which can be called an adhesive layer) into the outer layer of the artificial auricle, significantly improving the fit and stability of the artificial auricle with surrounding tissues during implantation, without adversely affecting its mechanical strength and biocompatibility. In the artificial auricle casting process, this invention designs glycerol as a release agent coated on the outermost layer, effectively simplifying the demolding operation and maximizing the preservation of the integrity and morphological fidelity of the auricle's fine structure. The multi-coating demolding technology used in this invention endows the resulting artificial auricle with a layered structure and multifunctional synergy, highlighting the advantages of each functional layer. In terms of mold design, its diameter is optimized to be no less than 1.5 cm to avoid the problem of missing details during mechanical polishing due to excessively small size, and the increased difficulty of the coating-demolding process. The optimal concentration of the outer HAMA-DA adhesive layer has been experimentally verified to be 3-5%. The concentration of wt% ensures good tissue adhesion while avoiding problems such as coating thickening, increased bubbles, and demolding difficulties caused by excessive concentration. This invention uses a casting process to replace the direct cell-loaded bio-ink 3D printing method, effectively avoiding cell damage caused by shear force and thermal effects, and is more conducive to the implementation of multi-layer coating processes. In addition, this casting method shows significant advantages over bioprinting in terms of structural resolution, process controllability, and success rate, which is of great value and clinical significance for promoting the clinical translation of artificial auricle materials.

[0020] 5) The innovative method of preparing the casting mold involves acquiring multi-view depth data of the auricle using LiDAR, and then performing three-dimensional fusion, point cloud super-resolution, and feature-preserving re-mesh processing to construct a high-precision auricle mold model. This enables personalized customization and high-precision contouring of the auricle mold, making the design and preparation technology of the artificial auricle in this invention universal and applicable to all age groups and different patient groups, meeting their aesthetic needs and possessing great clinical value and practical significance. Attached Figure Description

[0021] Figure 1 A schematic diagram of the fabrication process for tissue-adhesive chondrogenic bilayer artificial auricle material; Figure 2 The images show actual artificial auricle molds, with (a) and (b) being views from different angles. Figure 3 To prepare the obtained double-layer artificial auricle material. Detailed Implementation

[0022] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. All materials not specifically mentioned in this invention are readily available. The porous GelMA used has a pore size of 100-200 μm. The preparation process of the tissue-adhesive chondrogenic double-layer artificial auricle material of the present invention is as follows: Figure 1 As shown, the artificial auricle mold obtained in Example 1 and the prepared double-layer artificial auricle material are as follows. Figure 2 , Figure 3 As shown.

[0023] Comparative Example 1: 1) Design and fabrication of artificial auricle mold: Depth data of the patient's healthy auricle was acquired using a LiDAR-equipped mobile device. The data was then reconstructed using 3D fusion, point cloud super-resolution, and feature-preserving remeshing to generate a 3D model file in OBJ format. This file was imported into Blender software. Based on this model file, the corresponding auricle mold structure was designed. This file was saved as an STL file for printing, and the artificial auricle was cast into a mold using transparent resin as the material through photopolymerization.

[0024] 2) Preparation of the casting solution: A 5wt% HAMA solution was used as the dispersed phase and Novec 7500 fluorinated oil as the continuous phase using a flow-focusing connected microfluidic chip. At 37°C, a micropump controlled the flow rate of the dispersed phase at 4µL / min and the continuous phase at 20µL / min, resulting in HAMA microdroplets with a diameter of approximately 50-100µm, forming a W / O microemulsion. This was cross-linked and cured by 410nm UV irradiation for 120s, followed by diethyl ether phase separation, washing with deionized water, and lyophilization to obtain HAMA microsphere powder. Under sterile, light-protected conditions and at 60°C, porous GelMA material and HAMA microsphere powder were dissolved in a PBS solution containing 0.25wt% LAP to prepare a porous GelMA solution containing 5% HAMA microspheres. The solution was cooled to 37°C, and MSCs (within the P2-P4 generation range) were added at a rate of 1×10⁻⁶. 7 A concentration of 1 / mL was dispersed in the above solution to obtain a porous GelMA composite slurry for casting artificial auricles.

[0025] 3) Casting and molding of artificial auricle: The porous GelMA composite slurry loaded with MSCs and HAMA microspheres was poured into an artificial auricle mold and photocured using a 410nm UV light source with a power of 20 mW / cm². 2 The irradiation time is 30 seconds. After the irradiation is completed, the casting material is demolded, rinsed and dried to obtain the artificial auricle.

[0026] 4) In vitro chondrogenic differentiation of artificial auricles: The obtained artificial auricle structures were placed in intact culture medium [DMEM-H, 10% FBS, 100 U / mL penicillin, 0.1 mg / mL streptomycin and 10 ng / mL TGF-β3] for culture. The culture medium was changed every 3 days and cultured continuously for 21 days to obtain artificial auricles.

[0027] 5) In vivo culture of artificial auricles: SD rats were selected as implantation subjects. A 3cm longitudinal incision was made in the middle of the back. Subcutaneous bags were bluntly dissected on both sides of the incision and implanted. One of the above-mentioned artificial auricles was implanted on each side. After suturing the incision, the rats were fed normally for 8 weeks.

[0028] 6) Sections of the aforementioned artificial auricle were examined under a confocal microscope using live-dead staining. Numerous clusters of cells were observed within the framework, with 41% exhibiting red fluorescence and 59% showing green fluorescence, indicating the presence of a large number of necrotic cores. Toluidine blue staining of the sections to label MSCs, observed under a confocal fiber microscope, revealed that only less than 15% of the cells were labeled, and they were randomly distributed throughout the sections. Furthermore, subcutaneous implantation of the artificial auricle in SD rats resulted in auricle displacement, poor adhesion to the epidermis in some areas, and poor aesthetics. These observations suggest that this type of artificial auricle material suffers from low nutrient and waste exchange capacity of internal mesenchymal stem cells, leading to low cell survival and low cartilage differentiation efficiency. Moreover, the auricle exhibits poor adhesion to surrounding tissues after subcutaneous implantation, and displacement occurs with the patient's movement, affecting aesthetics and surgical outcomes.

[0029] Example 1: 1) Design and fabrication of artificial auricle mold: Depth data of the patient's healthy auricle was acquired using a LiDAR-equipped mobile device. The data was then reconstructed using 3D fusion, point cloud super-resolution, and feature-preserving remeshing to generate a 3D model file in OBJ format. This file was imported into Blender software. Based on this model file, the corresponding auricle mold structure was designed. This file was saved as an STL file for printing, and the artificial auricle was cast into a mold using transparent resin as the material through photopolymerization.

[0030] 2) Construction of Inner and Outer Layer Materials: Outer Layer Material: HAMA was obtained by methacrylation, and then synthesized as a dopamine-methacryl bifunctional HAMA-DA polymer by EDC / NHS-mediated carboxylimide coupling reaction with dopamine hydrochloride. A 5wt% HAMA-DA solution was prepared by adding 0.25wt% LAP under light-protected conditions, serving as the outer coating material. Inner Layer Material: A 5wt% HAMA solution was used as the dispersed phase and Novec 7500 fluorinated oil as the continuous phase using a flow-focusing connected microfluidic chip. The flow rate of the dispersed phase was controlled at 4µL / min and the continuous phase at 20µL / min by a micropump at 37°C. The resulting HAMA microdroplets had a diameter of approximately 50-100µm, forming a W / O microemulsion. Crosslinking and curing were achieved by 410nm UV irradiation for 120s, followed by diethyl ether phase separation, washing with deionized water, and lyophilization to obtain HAMA microsphere powder. HAMA microspheres were immersed in a 0.1 mM Kartogenin DMSO solution and reacted in a sealed environment for 24 h. After rinsing with PBS, the microspheres were aged for 12 h to complete drug loading. Under sterile, light-protected conditions and at 60°C, GelMA material and drug-loaded HAMA microsphere powder were dissolved in a PBS solution containing 0.25 wt% LAP to prepare a porous GelMA solution containing 5% drug-loaded HAMA microspheres. The solution was cooled to 37°C, and MSCs (within the P2-P4 generation range) were loaded at a rate of 1 × 10⁻⁶. 7 A concentration of 1 / mL is dispersed in the above solution to obtain a porous GelMA composite slurry, forming an inner layer composite slurry.

[0031] 3) Multi-coating molding of artificial auricle: A 50% (w / w) glycerol solution and the above-mentioned 5wt% HAMA-DA solution are sequentially coated on the surface of the mold, and pre-cured by irradiation with a 410nm UV light source for 15s; then a porous GelMA composite slurry carrying MSCs and drug-loaded HAMA microspheres is poured in, and a second curing is performed by UV irradiation for 15s; finally, a 0.5mm thick HAMA-DA layer with a concentration of 5wt% is coated on the free surface of the pre-cured slurry, and finally cured and shaped for 20s. The above-cured artificial auricle is shaken to demold, rinsed 3 times with PBS and dried with sterile nitrogen to obtain an artificial auricle material with a multi-composite structure.

[0032] 4) In vitro chondrogenic differentiation of artificial auricles: The obtained artificial auricle materials were placed in a complete culture medium [DMEM-H, 10% FBS, 100 U / mL penicillin, 0.1 mg / mL streptomycin and 10 ng / mL TGF-β3] for culture. The culture medium was changed every 3 days and cultured continuously for 21 days to obtain artificial auricles.

[0033] 5) In vivo culture of artificial auricles: SD rats were selected as the model. A 3cm longitudinal incision was made in the middle of the back. The sacs were bluntly dissected on both sides of the incision and implanted. One of the above-mentioned artificial auricles was implanted on each side. After suturing the incision, the rats were fed routinely for 8 weeks.

[0034] 6) Compared to Comparative Example 1, Example 1 involved coating the surface of the artificial auricle with a tissue adhesion layer and loading a cartilage differentiation-promoting drug onto an inner microsphere structure. Sectioning of the tissue adhesion-type double-layered artificial auricle structure and observing under a confocal microscope using live-dead staining revealed that almost all cells exhibited green fluorescence, accounting for as high as 93%, indicating good cell survival in this type of substrate. Toluidine blue staining of the sections to label MSCs revealed that 84% of the cells were uniformly labeled with blue dye under a confocal fiber microscope. These phenomena suggest that MSCs are uniformly and densely differentiated and exhibit good cartilage morphology. Furthermore, compared to Comparative Example 1, the artificial auricle of Example 1 did not exhibit auricle displacement after subcutaneous implantation, resulting in better aesthetics and surgical outcomes. This structure provides the most basic histological foundation for the long-term stable in-situ survival of this type of artificial auricle in vivo.

[0035] Example 2: Artificial Auricle Mold Fabrication: First, a high-resolution CT scan of the patient's auricle structure is used to obtain accurate two-dimensional image data. Then, the obtained data is imported into MIMICS software, where the soft tissue area of ​​the auricle is extracted after trimming and segmentation to obtain the contour and structural information of the auricle and complete the reconstruction of the three-dimensional model. The obtained three-dimensional model is imported into CAD software, and after structural adjustment and optimization, the corresponding auricle mold structure design is completed. The file is saved as an STL file for printing, and the artificial auricle is cast into a mold using transparent resin as the material through photocuring.

[0036] 2) Construction of Inner and Outer Layer Materials: Outer Layer Material: HAMA was obtained by methacrylation, and then synthesized as a dopamine-methacryl bifunctional HAMA-DA polymer by EDC / NHS-mediated carboxylimide coupling reaction with dopamine hydrochloride. A 5wt% HAMA-DA solution was prepared by adding 0.25wt% LAP under light-protected conditions, serving as the outer coating material. Inner Layer Material: A 5wt% HAMA solution was used as the dispersed phase and Novec 7500 fluorinated oil as the continuous phase using a flow-focusing connected microfluidic chip. The flow rate of the dispersed phase was controlled at 4µL / min and the continuous phase at 20µL / min by a micropump at 37°C. The resulting HAMA microdroplets had a diameter of approximately 50-100µm, forming a W / O microemulsion. Crosslinking and curing were achieved by 410nm UV irradiation for 120s, followed by diethyl ether phase separation, washing with deionized water, and lyophilization to obtain HAMA microsphere powder. HAMA microspheres were immersed in a 0.1 mM Kartogenin DMSO solution and reacted in a sealed environment for 24 h. After rinsing with PBS, the microspheres were aged for 12 h to complete drug loading. Under sterile, light-protected conditions and at 60°C, GelMA material and drug-loaded HAMA microsphere powder were dissolved in a PBS solution containing 0.25 wt% LAP to prepare a porous GelMA solution containing 5% drug-loaded HAMA microspheres. The solution was cooled to 37°C, and MSCs (within the P2-P4 generation range) were loaded at a rate of 1 × 10⁻⁶. 7 A concentration of 1 / mL is dispersed in the above solution to obtain a porous GelMA composite slurry, forming an inner layer composite slurry.

[0037] 3) Multi-coating molding of artificial auricle: A 50% (w / w) glycerol solution and the above-mentioned 5wt% HAMA-DA solution are sequentially coated on the surface of the mold, and pre-cured by irradiation with a 410nm UV light source for 15s; then a porous GelMA composite slurry carrying MSCs and drug-loaded HAMA microspheres is poured in, and a second curing is performed by UV irradiation for 15s; finally, a 0.5mm thick HAMA-DA layer with a concentration of 5wt% is coated on the free surface of the pre-cured slurry, and finally cured and shaped for 20s. The above-cured artificial auricle is shaken to demold, rinsed 3 times with PBS and dried with sterile nitrogen to obtain an artificial auricle material with a multi-composite structure.

[0038] 4) In vitro chondrogenic differentiation of artificial auricles: The obtained artificial auricle materials were placed in a complete culture medium [DMEM-H, 10% FBS, 100 U / mL penicillin, 0.1 mg / mL streptomycin and 10 ng / mL TGF-β3] for culture. The culture medium was changed every 3 days and cultured continuously for 21 days to obtain artificial auricles.

[0039] 5) In vivo culture of artificial auricles: SD rats were selected as the model. A 3cm longitudinal incision was made in the middle of the back. The sacs were bluntly dissected on both sides of the incision and implanted. One of the above-mentioned artificial auricles was implanted on each side. After suturing the incision, the rats were fed routinely for 8 weeks.

[0040] 6) Compared to Comparative Example 1, Example 2 used a traditional three-dimensional reconstruction method to obtain the required auricle mold structure. The constructed auricle shape largely replicated the patient's auricle morphology; however, it exhibited coarseness in terms of fine auricle structure, with some loss of microstructures. Sectioning the tissue-adhesive double-layer artificial auricle structure and using live-dead staining under a confocal microscope revealed that almost all cells were green fluorescent, accounting for as much as 91%, indicating good cell survival in this type of substrate. Toluidine blue staining of the sections to label MSCs revealed that 85% of the cells were uniformly labeled with blue dye under a confocal fiber microscope. These findings suggest that MSCs are uniformly and densely differentiated and exhibit good cartilage morphology. Furthermore, compared to Comparative Example 1, the artificial auricle in Example 2 did not show auricle position migration after subcutaneous implantation. These results indicate that the artificial auricle obtained in Example 2 performed worse than that in Example 1 in terms of fine structure acquisition, conformity of the formed structure, and auricle detail presentation, affecting the aesthetics of the final auricle structure, but still basically meeting the histobiological requirements for in vivo survival of the artificial auricle.

[0041] Example 3: 1) Design and fabrication of artificial auricle mold: Depth data of the patient's healthy auricle was acquired using a LiDAR-equipped mobile device. The data was then reconstructed using 3D fusion, point cloud super-resolution, and feature-preserving remeshing to generate a 3D model file in OBJ format. This file was imported into Blender software. Based on this model file, the corresponding auricle mold structure was designed. This file was saved as an STL file for printing, and the artificial auricle was cast into a mold using transparent resin as the material through photopolymerization.

[0042] 2) Construction of Inner and Outer Layer Materials: Outer Layer Material: HAMA was obtained by methacrylation. It was then combined with dopamine hydrochloride via an EDC / NHS-mediated carboxylimide coupling reaction to synthesize a dopamine-methacryl bifunctional HAMA-DA polymer. Under light-protected conditions, 0.25 wt% LAP was added to prepare a 5 wt% HAMA-DA outer coating material. Inner Layer Material: A 5 wt% HAMA solution was used as the dispersed phase and Novec 7500 fluorinated oil as the continuous phase using a flow-focusing connected microfluidic chip. At 37°C, a micropump controlled the flow rate of the dispersed phase at 4 µL / min and the continuous phase at 20 µL / min, resulting in HAMA microdroplets with a diameter of approximately 50-100 µm, forming a W / O microemulsion. This was cross-linked and cured by 410 nm UV irradiation for 120 s, followed by diethyl ether phase separation, washing with deionized water, and lyophilization to obtain HAMA microsphere powder. HAMA microspheres were immersed in a 0.1 mM Kartogenin DMSO solution and reacted in a sealed environment for 24 h. After rinsing with PBS, the microspheres were aged for 12 h to complete drug loading. Under sterile, light-protected conditions and at 60°C, non-porous GelMA material and drug-loaded HAMA microsphere powder were dissolved in a PBS solution containing 0.25 wt% LAP to prepare a GelMA solution containing 5% drug-loaded HAMA microspheres. The solution was cooled to 37°C, and MSCs (within the P2-P4 generation range) were loaded at a rate of 1 × 10⁻⁶. 7 A concentration of 1 / mL is dispersed in the above solution to form an inner layer of GelMA composite slurry.

[0043] 3) Multi-coating molding of artificial auricle: A 50% (w / w) glycerol solution and the above-mentioned 5wt% HAMA-DA solution are sequentially coated on the surface of the mold, and pre-cured by irradiation with a 410nm UV light source for 15s; then, a GelMA composite slurry with MSCs and drug-loaded HAMA microspheres is poured in, and a second curing is performed by UV irradiation for 15s; finally, a 0.5mm thick HAMA-DA layer with a concentration of 5wt% is coated on the free surface of the pre-cured slurry, and finally cured and shaped for 20s. The above-cured artificial auricle is shaken to demold, rinsed 3 times with PBS and dried with sterile nitrogen to obtain an artificial auricle material with a multi-composite structure.

[0044] 4) In vitro chondrogenic differentiation of artificial auricles: The obtained artificial auricle materials were placed in a complete culture medium [DMEM-H, 10% FBS, 100 U / mL penicillin, 0.1 mg / mL streptomycin and 10 ng / mL TGF-β3] for culture. The culture medium was changed every 3 days and cultured continuously for 21 days to obtain artificial auricles.

[0045] 5) In vivo culture of artificial auricles: SD rats were selected as the model. A 3cm longitudinal incision was made in the middle of the back. The sacs were bluntly dissected on both sides of the incision and implanted. One of the above-mentioned artificial auricles was implanted on each side. After suturing the incision, the rats were fed routinely for 8 weeks.

[0046] 6) Compared to Example 1, Example 2 used non-porous GelMA material as the inner matrix instead of porous GelMA. Sections of the in vitro cultured artificial auricle structure were examined using a confocal microscope with live-dead staining, revealing a cell viability of 83%. Toluidine blue staining of the sections to label MSCs showed a cartilage differentiation rate of 71%, both slightly lower than in Example 1. No significant migration was observed in the artificial auricle cultured for 8 weeks in vivo. The results indicate that the non-porous GelMA structure, to some extent, restricts cell migration and nutrient and gas exchange, leading to a decrease in cell viability and cartilage differentiation capacity compared to Example 1, but still basically meeting the basic histological requirements for in vivo survival of artificial auricles.

[0047] Example 4: 1) Design and fabrication of artificial auricle mold: Depth data of the patient's healthy auricle was acquired using a LiDAR-equipped mobile device. The data was then reconstructed using 3D fusion, point cloud super-resolution, and feature-preserving remeshing to generate a 3D model file in OBJ format. This file was imported into Blender software. Based on this model file, the corresponding auricle mold structure was designed. This file was saved as an STL file for printing, and the artificial auricle was cast into a mold using transparent resin as the material through photopolymerization.

[0048] 2) Construction of Inner and Outer Layer Materials: Outer Layer Material: HAMA was obtained by methacrylation, and then synthesized as a dopamine-methacryl bifunctional HAMA-DA polymer by EDC / NHS-mediated carboxylimide coupling reaction with dopamine hydrochloride. A 5wt% HAMA-DA solution was prepared by adding 0.25wt% LAP under light-protected conditions, serving as the outer coating material. Inner Layer Material: Under sterile, light-protected conditions and heating at 60°C, porous GelMA material was dissolved in a PBS solution containing 0.25wt% LAP to prepare a 5% porous GelMA solution. The solution was cooled to 37°C, and MSCs (within the P2-P4 generation range) were added at a rate of 1×10⁻⁶. 7 A porous GelMA composite slurry was obtained by dispersing the slurry at a concentration of 1 / mL in the above solution, forming an inner layer composite slurry.

[0049] 3) Multi-coating molding of artificial auricle: A 50% (w / w) glycerol solution and the above-mentioned 5wt% HAMA-DA solution are sequentially coated on the surface of the mold, and pre-cured by irradiation with a UV light source of 410nm for 15s; then, a porous GelMA composite slurry carrying MSCs is poured in, and a second curing is performed by UV irradiation for 15s; finally, a 0.5mm thick HAMA-DA layer with a concentration of 5wt% is coated four times on the free surface of the pre-cured slurry, and finally cured and shaped for 20s. The above-cured artificial auricle is shaken to demold, rinsed 3 times with PBS and dried with sterile nitrogen to obtain an artificial auricle material with a multi-composite structure.

[0050] 4) In vitro chondrogenic differentiation of artificial auricles: The obtained artificial auricle materials were placed in a complete culture medium [DMEM-H, 10% FBS, 100 U / mL penicillin, 0.1 mg / mL streptomycin and 10 ng / mL TGF-β3] for culture. The culture medium was changed every 3 days and cultured continuously for 21 days to obtain artificial auricles.

[0051] 5) In vivo culture of artificial auricles: SD rats were selected as the model. A 3cm longitudinal incision was made in the middle of the back. The sacs were bluntly dissected on both sides of the incision and implanted. One of the above-mentioned artificial auricles was implanted on each side. After suturing the incision, the rats were fed routinely for 8 weeks.

[0052] 6) Compared to Example 1, Example 3 did not load the chondrogenic drug Kartogenin into the inner layer material. Sections of the unloaded bilayer artificial auricle were examined using confocal microscopy with live-dead staining. Almost all cells showed green fluorescence, accounting for 84%, indicating good cell compatibility. Toluidine blue staining showed that only 54% of cells were uniformly labeled with blue dye, significantly lower than in Example 1. These results suggest that although the bilayer auricle structure is beneficial for maintaining MSC survival, the lack of Kartogenin significantly reduces MSC chondrogenic differentiation efficiency, thus affecting the functional chondrogenic capacity of the artificial auricle in vivo.

Claims

1. A tissue-adhesive, chondrogenic, double-layered artificial auricle material based on multiple coating and UV curing processes. The preparation method of the [method] is characterized by, Includes the following steps: 1) Using microfluidic technology combined with impregnation process, methacrylated hyaluronic acid (HAMA) microspheres loaded with Kartogenin were constructed to obtain drug-loaded HAMA microspheres; 2) HAMA-DA molecules modified with dopamine and methacrylamide bifunctional groups were synthesized by methacrylation and carboxylimide coupling reaction, and the resulting solution was prepared to obtain HAMA-DA solution. 3) Based on LiDAR and 3D reconstruction technology, a high-fidelity artificial auricle mold is prepared by photopolymerization 3D printing; 4) Prepare a gelatin methacrylate (GelMA) solution and combine it with mesenchymal stem cells (MSCs) and drug-loaded HAMA microspheres under aseptic conditions at 35-37℃ to obtain a GelMA composite slurry; 5) Perform a multi-coating process on the mold surface: sequentially coat a glycerol layer, a HAMA-DA solution layer, a GelMA composite slurry layer containing MSCs and drug-loaded HAMA microspheres, and a HAMA-DA solution layer. During the coating process, perform preliminary UV curing and UV curing shaping, demold, rinse, and dry to obtain the artificial auricle material.

2. The method for preparing a tissue-adhesive chondrogenic double-layer artificial auricle material based on multiple coating and UV curing processes according to claim 1, characterized in that, In step 1), the microfluidic technology involves using a 3-5 wt% HAMA solution as the dispersed phase and Novec 7500 fluorinated oil as the continuous phase at 35-37°C. The flow rate of the dispersed phase is controlled at 2-4 µL / min, and the flow rate of the continuous phase is controlled at 10-20 µL / min to form a W / O microemulsion. This microemulsion is then cross-linked and cured by UV irradiation. After phase separation with diethyl ether, the microemulsion is washed with deionized water and freeze-dried to obtain HAMA microspheres. The UV irradiation source is 350-410 nm with a power of 20-40 mW / cm². 2 Irradiation time: 120-180 seconds.

3. The method for preparing a tissue-adhesive chondrogenic double-layer artificial auricle material based on multiple coating and UV curing processes according to claim 1, characterized in that, In step 1), Kartogenin loading is achieved through an impregnation process: HAMA microspheres are placed in a 0.1-0.2 mM Kartogenin / DMSO solution at 4-8°C and impregnated in a sealed environment for 6-24 h, and then aged for 6-12 h. After that, they are washed with PBS to complete the drug loading of HAMA microspheres.

4. The method for preparing a tissue-adhesive chondrogenic double-layer artificial auricle material based on multiple coating and UV curing processes according to claim 1, characterized in that: In step 2), HAMA-DA is prepared by a dual chemical grafting reaction: 1-2 wt% HA is dissolved in deionized water, the pH of the solution is adjusted to 7-8, and 20-25 times the molar excess of methacrylic anhydride relative to the hydroxyl group of HA is added. After reacting at room temperature for 4-6 hours, the solution is transferred to 4 °C and reacted for another 15-25 hours. After precipitation in cold ethanol, centrifugation, washing, and lyophilization, HAMA is obtained. Further, 1-2 wt% HAMA is dissolved in deionized water, the pH of the solution is adjusted to 4-5, and EDC / NHS is added to perform a secondary dopamine grafting modification with dopamine hydrochloride via a carboxylimide coupling reaction. The reaction is carried out in the dark for 4-8 hours, and the solution is transferred to deionized water for dialysis for 3-5 days, with the solution changed 3-6 times a day. After lyophilization, HAMA-DA is obtained.

5. The method for preparing a tissue-adhesive chondrogenic double-layer artificial auricle material based on multiple coating and UV curing processes according to claim 4, characterized in that: The molar ratio of EDC, NHS, and HAMA is 2:1:2-2:1:4, and the molar ratio of HAMA to dopamine hydrochloride is 1:0.5-1:

1. When dialyzing HAMA-DA, the molecular weight cutoff of the dialysis bag is 3.5 kDa. HAMA-DA is dissolved in deionized water to prepare a solution with a concentration of 3-5 wt%, and a photoinitiator is added with a concentration of 0.1-0.25 wt%. The dissolution process is carried out under light-protected conditions and at room temperature.

6. The method for preparing a tissue-adhesive chondrogenic double-layer artificial auricle material based on multiple coating and UV curing processes according to claim 1, characterized in that: In step 3), depth data and multi-view pose information of a healthy auricle are first collected using a LiDAR-equipped mobile device. Then, one or more methods based on multi-view stereo vision (MVS), Gaussian mixture model, and depth map fusion are used to fuse the multi-view images and depth information to generate an initial 3D model of the auricle. Subsequently, a point cloud / mesh super-resolution network is used to upsample the point cloud data corresponding to the initial 3D model and perform a feature-preserving remesh operation to improve the sampling density and geometric fidelity in the required areas. Then, based on the obtained refined 3D model, the negative mold structure is designed to obtain a high-precision, smooth-surfaced, and structurally complete 3D model of the artificial auricle casting mold. Finally, transparent photosensitive resin is used as the raw material, and 3D photopolymerization printing technology is used to print the transparent artificial auricle casting mold. After the mold is formed, it is polished until the surface roughness is less than 0.2µm.

7. The method for preparing tissue-adhesive chondrogenic double-layer artificial auricle material based on multiple coating and UV curing processes according to claim 1, characterized in that: In step 4), a porous GelMA solution with a concentration of 5-7.5 wt% is prepared by dissolving in a water bath at 60-80℃ under light-protected and sterile conditions. After complete dissolution, the solution is cooled to 35-37℃, filtered for sterilization, and P2-P4 generation MSCs and drug-loaded HAMA microspheres are added. The solution is then blown to homogenize, and a photoinitiator is added to obtain the GelMA composite slurry.

8. The method for preparing a tissue-adhesive chondrogenic double-layer artificial auricle material based on multiple coating and UV curing processes according to claim 7, characterized in that: The concentration of MSCs in the GelMA composite slurry is 1×10⁻⁶. 7 The concentration of drug-loaded HAMA microspheres was 3-5 wt%; the concentration of photoinitiator was 0.1-0.25 wt%.

9. The method for preparing a tissue-adhesive chondrogenic double-layer artificial auricle material based on multiple coating and UV curing processes according to claim 1, characterized in that: Step 5) specifically involves: first, coating the surface of the artificial auricle mold with a glycerol layer; then coating a HAMA-DA solution layer with a thickness of 0.25-1 mm, and pre-curing it with UV for 10-15 seconds. Then coat it with the porous GelMA composite slurry and allow it to cure under UV for 10-15 seconds. The HAMA-DA layer with a thickness of 0.25-1 mm is then coated onto the free surface of the pre-cured slurry. After final curing and shaping for 15-20 seconds, the artificial auricle is demolded by vibration, rinsed with PBS, and dried with sterile nitrogen to obtain the artificial auricle material.

10. A tissue-adhesive, chondrogenic, double-layered artificial auricle material based on a multi-coating and UV-curing process, characterized in that, It is prepared by the method described in any one of claims 1-9.